Machiavelli - Ikhwan, Ikhwan (Al-Ijtima`i: International Journal of Government and Social Science, 2016)
Politic is the agenda of authority and power, but the most important thing of politics is how to rule or stay on power as long as possible and this stay on power thing is coloring most of human history by blood, war, destruction, and annihilation. Many terms coined from the absurdity of people try to gain the authority such as ethnic cleansing, genocide, atrocities, coup de tat, and many others, those terms show that human being is drawn into power and the possibility to rule other people as an absolute ruler, the discussion about politic should be seen from the perspective of human being willingness to be a ruler, seeing politic from morality agenda would be false and wrong because politic (how to rule people) is nothing to do with moral or ethical, even though many philosophers such as Plato and Al Faraby stood on the moral ground of politic is still unable to change the true face of politic, the power. Machiavelli, on the other hand, is not trying to beautify politic as a peak of civilization, but just an animal instinct of human being of pursuing alpha male status, and Machiavelli understood and explain to people how to be an effective ruler, but like in animal kingdom, an effective alpha male is the one who willing to draw the blood.